MADS-Box and bHLH Transcription Factors Coordinate Transmitting Tract Development in Arabidopsis thaliana - Di Marzo, Maurizio; Roig-Villanova, Irma; Zanchetti, Eva; Caselli, Francesca; Gregis, Veronica; Bardetti, Paola; Chiara, Matteo; Guazzotti, Andrea; Caporali, Elisabetta; Mendes, Marta Adelina; Colombo, Lucia; Kater, Martin M. (Frontiers in Plant Science, 2020)
The MADS-domain transcription factor SEEDSTICK (STK) controls several aspects of plant reproduction. STK is co-expressed with CESTA (CES), a basic Helix-Loop-Helix (bHLH) transcription factor-encoding gene. CES was reported to control redundantly with the brassinosteroid positive signaling factors BRASSINOSTEROID ENHANCED EXPRESSION1 (BEE1) and BEE3 the development of the transmitting tract. Combining the stk ces-2 mutants led to a reduction in ovule fertilization due to a defect in carpel fusion which, caused the formation of holes at the center of the septum where the transmitting tract differentiates. Combining the stk mutant with the bee1 bee3 ces-2 triple mutant showed a clear enhancement of the number of unfertilized ovules and septum defects. The transcriptome profile of this quadruple mutant revealed a small subset of deregulated genes which are mainly involved in cell death, extracellular matrix and cell wall development. Our data evidence a regulatory gene network controlling transmitting tract development regulated directly or indirectly by a STK-CES containing complex and reveal new insights in the regulation of transmitting tract development by bHLH and MADS-domain transcription factors.